Polo-like kinase phosphorylation of bilobe-resident TbCentrin2 facilitates flagellar inheritance in Trypanosoma brucei - de Graffenried, Christopher L. (The American Society for Cell Biology, 2013)
In the protist parasite Trypanosoma brucei, the single Polo-like kinase (TbPLK) controls the inheritance of a suite of organelles that help position the parasite's single flagellum. These include the basal bodies, the bilobe, and the flagellar attachment zone (FAZ). TbCentrin2 was previously shown to be a target for TbPLK in vitro, and this is extended in this study to in vivo studies, highlighting a crucial role for serine 54 in the N-terminal domain. Duplication of the bilobe correlates with the presence of TbPLK and phospho-TbCentrin2, identified using phosphospecific antiserum. Mutation of S54 leads to slow growth (S54A) or no growth (S54D), the latter suggesting that dephosphorylation is needed to complete bilobe duplication and subsequent downstream events necessary for flagellum inheritance.